Analisis Pengaruh Online Review di Youtube, Citra Merek, dan Persepsi Harga terhadap Keputusan Pembelian Smartphone Oppo - Brian Luyzh Fernando Giri; Ida Bagus Nyoman Udayana; Bernadetta Diansepti Maharani (Universitas Batanghari, 2022)
This study aims to determine the effect of Online Review (X1) on Yotube, Brand Image (X2), and Price Perception (X3) on the Purchase Decision (Y) of Oppo Smartphones. This type of research is a quantitative research by taking samples from students of the Faculty of Economics, Universitas Sarjanawiyata Tamansiswa Yogyakarta batch 2019 - 2020, as many as 93 people who have purchased Oppo brand smartphones as research subjects. Sampling used purposive sampling technique, and data collection was carried out by survey method by distributing questionnaires. The data was processed using the SPSS application by conducting data quality tests, classical assumption tests, multiple regression tests, t tests and coefficients of determination tests. Based on the test results in this research, it shows that the Online Review variable on YouTube and the price perception have a positive and significant effect on the Oppo Smartphone Purchase Decision. While the Brand Image variable has a positive but not significant effect on the Oppo Smartphone Purchase Decision.